Factors related to buying habits of working women as encouraged by fashion forecasting in fashion magazines - Larrazabal, Ma. Esperanza Y.; Escano, Maria Monica R. (2001.)
The modern woman is now competing with men in the world of business. They have come a long way to climbing the ladder of success in this type of field. Faced with different responsibilities now, they have to be more conscious of how they present themselves in front of their clients. One of the best ways to present themselves appropriately is through their clothing. Women, specifically the working class are very conscious of how they look. To keep up with the ever-changing world of fashion, they tend to browse through magazines to give them the latest scoops of today's hottest trends. It is not hard to notice that here in the Philippines, there are growing numbers of local fashion magazines. This will show that women here are becoming more very conscious of their appearance. The study will find out if working women really do take notice of the trends these magazines present. Fashion magazines are important references for women. They can learn to discern fashion trends from these magazines. It gives them ideas on what to expect for the coming months and how to incorporate these fashion ideas to their wardrobe. There is always a question though if women, who read these magazines follow their forecasts. Will they actually purchase the fashion items being presented in the fashion forecasts? Do they think of them as up-to-date and informative? The research aims to find out if fashion forecasts in fashion magazines is related to the buying habits of selected working women in some areas in Metro Manila. Specifically, this study intend to: a) determine if the information working women get from fashion magazines through their fashion forecasts affect their buying habits; b) determine if factors such as color, theme, fabric, silhouette, and style of the fashion forecasts influence buying preferences of working women; and determine if age and income relates to buying preferences of working women based on the fashion forecast in the magazine. Results of this study will be of great significance to the fashion magazines for them to know which of their fashion forecasts have more impact on the buying habits of the working women who read their magazines. This knowledge will let them know which of their forecasts should be given more emphasis on as well as to improve on the factors that do not attract the reader's taste. It will also inform them at what age and income bracket they are most influential so they would be able to adjust more on to that level and improve their forecasts for it to relate to the other income and age brackets. It will also be of significance to local manufacturers for them to know if fashion forecasts will give them an idea of what to produce if research will show that forecasts really encourage working women to purchase garments based on what they read. The study was conducted by using purposive sampling of 40 Filipino working women, single or married who read and buy fashion magazines constantly coming from different offices in Metro Manila. This assured the researcher that the working women chosen to do the survey are the ones who buy or read magazines regularly. Purposive sampling was used and selection was based according to their age and income bracket. This type of sampling was used to find the relationship of age and income to the buying habits of working women with regard to the fashion forecasts that they read. Survey forms were given to the working women chosen by the researcher for the data. Seventy-five percent of the women who answered the survey have purchased garment pieces based on the fashion forecasts that they read in fashion magazines. Though they follow the suggestions given by the fashion magazines, they would still buy the clothes of similar style to the product being forecasted and not the exact product itself was featured in the magazine. Most factors of the fashion forecasts such as color, fabric, silhouette, style/look, and theme have the same effect on the buying habits of all the age and income group of the working women when sampled. Color ans style were the factors that were most influential while the theme factor had the least influence and for some no influence at all.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Consumer behavior -- Philippines; Fashion -- Forecasting